Application features of educational quests in the format of blended learning in higher educational establishments - Ulishchenko, Violetta; Kefeli-Yanovska, Olena; Ulishchenko, Andrij (My University, 2022)
In the process of work with students (postgraduate students, interns, teachers), the application of interactive forms of work has proven its effectiveness and relevance. At the same time, we should expand the methodological diversity of the interactive, involve such forms of work that best as possible meet the needs of the blended learning format. Quest as an interactive technology has many advantages – from a collective goal setting, definition of a strategy of movement to coordinated performance of intermediate tasks, search for substantiations and presentation of a collective decision. The main thing is that there are no obstacles to the realization of the educational quest, such as online or offline, because the help comes from the interactive board Miro. The purpose of the work is to substantiate the peculiarities of the application of the educational quest as a game technology in blended and distance education with the goal of deepening the motivation of students of higher education institutions of Ukraine, in particular medical ones; to intensify scientific research activities, to improve interaction in groups and teams, to promote the development of clinical thinking and communicative competence. Research methods. Theoretical (processing of the source base) and empirical (development and implementation of didactic quests in educational activities) research methods were used in the work. Due to the combination of these components, the expediency of application of quest-technologies in a blended form of education in higher education institutions is substantiated. Conclusions. Thanks to the involvement of quests, those who study will not only save motivation, but they will also structure, renew, update the acquired knowledge for further professional growth. Quests do not require students to be physically present in the classroom, and under the condition of a proper organization (script, route sheets for teams), the final result of their conducting in the format of blended education (through ZOOM, MIRO, another online platform for group work) is quite high. It is also interesting to note that quests in the form close to the competition, provide the opportunity to carry out summative and formative assessment, which is extremely important for monitoring the quality of knowledge. The application of educational quests in higher medical education with the involvement of interactive online boards opens up the opportunity to provide active interaction of subjects of training in conditions of a blended format. During the quest, the teacher performs the functions of a moderator, since organizational moments and the working atmosphere during group communication depend on him, as well as possible help in the form of vector direction (if the discussion has reached a dead end), and substantiation of the final results.
Keywords: interactive forms of education; quest-technologies; educational quest; on-line board Miro; assessment; medical education; кафедра ділової іноземної мови та міжнародної комунікації